Contesting Religious Family Rights: Muslim and Hindu Women’s Land Ownership in Java and Bali - Achmad Fawaid; Busro Busro (Islam Realitas: Journal of Islamic and Social Studies, 2019)
This article depicts issues of the connection between women’s status and their roles in landownership in Java and Bali. In Java, for example, despite the fact that they are fortified by family law, just around one-third of land ownership belongs to women. In Bali, the Hindu women need to comply with the standard law in which they deal with a dilemma between their privileges and their reliability towards their families, networks, and culture. The absence of women's land ownership, either by the customary law or by the land enrollment, shows that the agrarian approach of land enlistment consistently gets women into the lower status of their legal ownership. Additionally, it impacts on the manners in which they practice religious convictions as they are situated in troublesome way of any legal issues, including family law (hukum keluarga) and inheritance rights (hak waris). Not with standing the Javanese government's endeavors to teach the general population about land enrollment and a couple of Hindu families to move a component from parent to little girl through a deed of offer before the land deed official, a few women know about the registration phases and the religious instrument of legacy rights. Subsequently, the manners in which Java and Bali women' inclinations are not bargained in political, social, and religious aspects. This article concludes that formal methodology for the exchange of land ownership when land is sold or partitioned in Bali, and also, standard Javanese practices in which insurance to the possibility of marital goods is given.Artikel ini berusaha menjelaskan hubungan antara status wanita dalam konteks agama dan peran mereka dalam kepemilikan tanah di Jawa dan Bali. Di Jawa, misalnya, meskipun kondisi mereka diperkuat oleh hukum keluarga, hanya sepertiga dari sertifikat tanah yang beratasnamakan perempuan. Sebaliknya, perempuan di Bali harus mengikuti hukum adat yang menghadapkan mereka pada dilema antara kebutuhan sehari-harinya di saatu sisi dan kepatuhannya terhadap keluarga, masyarakat, dan kebudayaan lokal di sisi lain. Minimnya kepemilikan tanah oleh perempuan ini, baik yang disebabkan oleh hukum adat maupun oleh hukum formal, memperlihatkan bahwa kebijakan pertanahan seringkali menempatkan mereka dalam status yang inferior. Mereka sama-sama menghadapi kesulitan di hadapan hak waris maupun hukum keluarga. Sekalipun di Jawa sudah ada sosialisasi terkait pendaftaran tanah dan di Bali sedikit dari mereka yang memberikan hak kepemilikannya kepada anak perempuannya, mereka tetap saja masih belum banyak memahami prosedur registrasi tersebut dan semakin marjinal dalam kepemilikan tanah dari hak waris. Kondisi ini memperlihatkan bagaimana perempuan Jawa dan Bali tidak terlalu diperhitungkan dalam ranah kebudayaan, politik, dan agama. Artikel ini akhirnya berkesimpulan bahwa perlu ada prosedur penjaminan tanah ketika tanah itu dibagikan di Bali, dan perlu ada jaminan keamanan terhadap hak-hak waris dalam adat Jawa